"Wheelchair" patients with nonorganic disease: a psychological inquiry. - Davison, P; Sharpe, M; Wade, D; Bass, C (1999)
We studied ten patients referred from the neurology service with severe disability associated with the use of a wheelchair, but with no organic disorder to account for their disabilities. All patients were assessed using rating scales as well as a standardized psychiatric interview (SCID), and all medical and psychiatric case notes were examined. We also interviewed key carers for their views on the information and assistance the patients had received. All but two of the ten patients were women, and the mean age was 45.4 years (SD=5.4). All had current diagnoses of conversion or somatoform disorders and six had previous episodes of major depression. Most patients expressed beliefs about their illness that were not consistent with the medical facts, and only two of the carers were satisfied with explanations they had been given by doctors. The results suggest that requests for psychiatric help once patients have become grossly disabled are unlikely to lead to recovery. The psychiatrist, however, can help the primary care doctor to formulate a plan of management aimed at preventing further deterioration.